Factors affecting the 27K DNA methylation pattern in asthmatic and healthy children from locations with various environments - Rossnerova, Andrea; Tulupova, Elena; Tabashidze, Nana; Schmuczerova, Jana; Dostal, Miroslav; Rossner, Pavel; Gmuender, Hans; Sram, Radim J (Mutation research, 2013)
Gene expression levels are significantly regulated by DNA methylation. Differences in gene expression profiles in the populations from various locations with different environmental conditions were repeatedly observed. In this study we compare the methylation profiles in 200 blood samples of children (aged 7-15 years) with and without bronchial asthma from two regions in the Czech Republic with different levels of air pollution (a highly polluted Ostrava region and a control Prachatice region). Samples were collected in March 2010 when the mean concentrations of benzo[a]pyrene (B[a]P) measured by stationary monitoring were 10.1±2.4ng/m(3) in Ostrava Bartovice (5.6 times higher than in the control region). Significantly higher concentrations of other pollutants (benzene, NO2, respirable air particles and metals) were also found in Ostrava. We applied the Infinium Methylation Assay, using the Human Methylation 27K BeadChip with 27,578 CpG loci for identification of the DNA methylation pattern in studied groups. Results demonstrate a significant impact of different environmental conditions on the DNA methylation patterns of children from the two regions. We found 9916 CpG sites with significantly different methylation (beta value) between children from Ostrava vs. Prachatice from which 58 CpG sites had differences >10%. The methylation of all these 58 CpG sites was lower in children from polluted Ostrava, which indicates a higher gene expression in comparison with the control Prachatice region. We did not find a difference in DNA methylation patterns between children with and without bronchial asthma in individual locations, but patterns in both asthmatics and healthy children differed between Ostrava and Prachatice. Further, we show differences in DNA methylation pattern depending on gender and urinary cotinine levels. Other factors including length of gestation, birth weight and length of full breastfeeding are suggested as possible factors that can impact the DNA methylation pattern in future life.
Keywords: dítě; mladiství; Case-Control Studies; Cotinine; Oligonucleotide Array Sequence Analysis; Male; bronchiální astma; Air Pollutants; studie případů a kontrol; lidé; biologické markery; Asthma; Czech Republic; Česká republika; Adolescent; ženské pohlaví; látky znečišťující vzduch; Biomarkers; kotinin; DNA Methylation; sekvenční analýza hybridizací s uspořádaným souborem oligonukleotidů; mužské pohlaví; metylace DNA; Child; Humans; Female